Study on the susceptibility to desertification of the Mucuri River Basin in Minas Gerais, Brazil (International Journal of Geoscience, Engineering and Technology, 2020)
Desertification is a process composed of natural and anthropic agents, its intensity and speed of development has increased in some regions due to changes in climate patterns, different ways of life and a bigger exploitation of natural resources. Therefore, an analysis of the desertification susceptibility in the Mucuri River Basin, in Minas Gerais, Brazil, was made through this study. A bibliographic revision was made about the subject to determine the theoretical and methodological procedures to be used, concepts of geoprocessing and its mapping tools were used during the analysis. The following attributes were adopted: slope, soil type, erosivity, vegetation cover and aridity. The results show areas with low and medium environmental susceptibility to erosion and desertification. It is concluded that the degradation of the Mucuri River Basin in Minas Gerais must be monitored and studied more attentively, so that the region does not face more severe economic and social problems.
Keywords: Geoprocessing; Desertification; Degradation